Kampanye Public Relations Bravetogether Komunitas Universitas Indonesia Sehat Mental Mengenai Perubahan Stigma Kesehatan Mental Remaja Indonesia: Studi Deskriptif Pada Komunitas Remaja Universitas Indonesia Sehat Mental - Della Fitria; Syifa Astasia Utari (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
Mental health is a person's mental condition, mental health disorders can be prevented through preventive movements, including the distribution of public knowledge and awareness regarding mental health through campaigns. The UISM community held a campaign in collaboration with the beauty brand Maybelline regarding mental health. This research discusses the #BraveTogether Public Relations Campaign of the Mentally Healthy University of Indonesia community regarding changes in the mental health stigma of Indonesian teenagers. The aim of holding this mental health campaign activity is to find out the campaign activities implemented by the UISM community in changing the mental health stigma of Indonesian teenagers, to find out what communication channels are used to carry out #BraveTogether Public Relations Campaign activities, to find out the results obtained in the Public Relations Campaign #BraveTogether. This research method uses a qualitative method with a descriptive research type, with interview data collection techniques. The results of the research show that the mentally healthy University of Indonesia community implemented the #BraveTogether public relations campaign, the mentally healthy University of Indonesia community in changing the mental health stigma of Indonesian teenagers, in carrying out its activities used the concept of a public relations campaign whose dimensions contained message content, message structure and audience response. Another thing used in this research is the theory of public relations campaign objectives which contains stages to make the target public think, determine attitudes and act in accordance with their wishes. The communication channels used were mass media, social media and face-to-face, the results obtained were to answer several research objectives to determine the mental health conditions of Indonesian teenagers and the enthusiasm of the people who participated in the #BraveTogether campaign activities.